Symmetrical polyhedron-bowl Co/CoO with hexagonal plate to forward electromagnetic wave absorption ability - Zhao, Biao; Li, Yang; Liu, Junwei; Fan, Lei; Gao, Ka; Bai, Zhongyi; Liang, Luyang; Guo, Xiaoqin; Zhang, Rui (CrystEngComm, 2019)
Symmetrical polyhedron-bowl (twin-hexagonal frustum-pyramid) structured Co/CoO products were prepared via a simple polyol reduction approach. The effects of reaction conditions (solvent constituents and reaction times) on the morphologies of Co/CoO products were investigated in detail. The microwave absorption performances of Co/CoO polyhedron paraffin composites with various Co/CoO contents were also studied. The results showed that the Co/CoO polyhedron paraffin composites exhibit enhanced microwave absorption properties with an increased Co/CoO content in the certain amount range. This phenomenon is observed because the conductive networks are gradually formed to cause leakage current loss with increasing Co/CoO content. However, the large leakage current induces impedance mismatch to prohibit microwaves from entering absorbers with a relatively high Co/CoO content. Thus, the Co/CoO polyhedrons paraffin composite with 50 wt% Co/CoO displays excellent microwave absorption properties. The optimal reflection loss (RL) is −45.3 dB at 12.5 GHz with a thickness of 1.7 mm. The effective absorption (below −10 dB) bandwidth can be tuned to the frequency of 4.5-18.0 GHz with thickness of 1.0-4.0 mm. The abundant reflection and scattering were caused by the symmetrical polyhedron-bowl structure. The micro-capacitors formed between Co/CoO as electrodes, paraffin as a dielectric, and the interfacial polarization collectively contribute to microwave absorption abilities. The symmetrical polyhedron-bowl structured Co/CoO displays enhanced microwave absorption properties.